Clinicopathological, endoscopic, and molecular characteristics of the “skirt” – a new entity of lesions at the margin of laterally spreading tumors - Osera, Shozo; Fujii, Satoshi; Ikematsu, Hiroaki; Miyamoto, Hideaki; Oono, Yasuhiro; Yano, Tomonori; Ochiai, Atsushi; Yoshino, Takayuki; Ohtsu, Atsushi; Kaneko, Kazuhiro (Endoscopy, 2016)
Background and study aim: A slightly elevated flat lesion with wide pits has occasionally been observed at the margin of laterally spreading tumors (LSTs) and is known as a “skirt.” The aim of this study was to evaluate the clinicopathological, endoscopic, and genetic characteristics of a skirt.Patients and methods: Consecutive LSTs were examined to evaluate the pathological, endoscopic, and genetic characteristics. Pathological characteristics, including the dimension of the cryptic opening (DCO), width of the individual gland (WIG), DCO to WIG ratio, and microvessel diameter were elucidated and compared with those of hyperplastic polyps, low grade dysplasia (LGD), and normal mucosa. The endoscopic findings of pit and microvascular patterns were assessed. Gene mutation analyses were performed for the KRAS, BRAF, NRAS, and PIK3CA genes.Results: A skirt was identified in 35 of 1023 LSTs, and 80 % of lesions with a skirt had a component of either intramucosal or submucosal adenocarcinoma. The DCO, WIG, and DCO to WIG ratio of the skirt were significantly larger than those of other lesions. The microvessel diameters in skirts were significantly smaller than those in LGDs. Regarding the endoscopic findings, 30 skirts showed pits with a coral reef-like appearance, and all skirt regions were found to have a type I capillary pattern. KRAS mutation at codon 146 was found in the nodular part in one of five LSTs with a skirt.Conclusion: The skirt is a newly identified lesion distinct from hyperplastic polyps and LGDs, suggesting the presence of a novel pathway for rectal carcinogenesis from LSTs with a skirt.